We're given the algebraic expression 2x^2 - 2z^4 + y^2 - x^2 + z^4
By hypothesis, x = -4, y = 3 and z = 2
Let's replace each letter by its given value:
2x^2 - 2z^4 + y^2 - x^2 + z^4
2(-4)^2 - 2(2)^4 + (3)^2 - (-4)^2 + (2)^4
(2*16) - 2*16 + 9 - 16 + 16
32 - 32 + 9 - 16 + 16
9
So wrong. The correct answer is not -3, but 9.
Hope this helps! :D
She made an error in the STEP 1
she shouldnt multiply the numbers
To make Ali brownies she will only be able to make 1/3
Answer:
Dividing each part into 10 and then summing the results up, is equivalent to dividing 89.5 into 10.
Step-by-step explanation:
This example refers to the Distributive Property of the division, which is valid when the dividend is decomposed.
A simple example could be: 400 ÷ 10 = (200 ÷ 10) + (200 ÷ 10)
In the exposed example we know that 89.5 = 80 + 9 + 0.5.
(80/10) + (9/10) + (0.5/10) =
8 + 0.9 + 0.05=
8.95
89.5/10 = 8.95